Follicle Cysts of the Ovary: A Report of 30 Cases of a Common Benign Lesion Emphasizing its Unusual Clinical and Pathologic Aspects. (July 2021) - Watkins, Jaclyn C.; Young, Robert H.
Abstract : The common ovarian follicle cyst is typically straightforward from both clinical and pathologic perspectives, but may have a variety of unusual features from both aspects at various stages of life. Lack of familiarity with these may lead to diagnostic quandaries, the most common of which is distinguishing between a follicle cyst and cystic granulosa cell tumor of either adult or juvenile type. We reviewed 30 cases of follicle cysts, all sent in consultation, to highlight unusual aspects of a common lesion. Patients ranged from 3 d to 47 yr old. Clinical presentations included precocious puberty, pelvic pain, or an incidentally discovered pelvic mass, including those occurring in neonates and in 2 adults with pituitary adenomas, one of which was diagnosed 3 yr after presentation with the ovarian cyst. Size ranged from 0.5 cm (deflated) to 18.5 cm, with 7 exceeding 8 cm in greatest dimension. Twelve cases demonstrated small satellite cystic follicles in the wall of the dominant cyst. The granulosa cell layer varied in thickness and mitotic activity (which ranged from 1 to 36 per 10 HPF), but uniformly displayed round nuclei that lacked nuclear grooves. Luteinization of the granulosa cell layer, theca layer, or both was seen across all clinical scenarios, with unluteinized cysts being most common in precocious puberty patients. This series documents that although typically smaller, a subset of follicle cysts are the same size as cystic granulosa cell tumors and the 2 entities may be grossly indistinguishable. Helpful clues to the diagnosis of follicle cyst are the lack of nuclear grooves (vs. adult granulosa cell tumor) and lack of invagination of granulosa cells into the cyst wall (vs. both forms of granulosa cell tumor). Mitoses in the granulosa cells are of no aid in the differential with either form of granulosa cell tumor as follicle cysts may exhibit brisk mitotic activity. Our series highlights some of the unusual clinical aspects, one relatively well known—an association with isosexual precocity, but 2 not as widely known, those occurring in neonates and those due to a pituitary adenoma, the latter sometimes not being discovered until a few years after presentation with a follicle cyst.